Sakral dan Profan dalam Kaitan dengan Ritus dan Tubuh: Suatu Telaah Filsafati Melalui Agama dan Konsep Diri - Subianto Bunyamin, Antonius (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2012)
Rationalism has led to the inability of capturing the presence of the divine in human activities. In such situations, the rites tend to be seen as a mere ceremonial activities and secularism pervades religious life in the believers’ ways of living of their faith. Secularism happens when people only look at the physical and material elements in the religious activities, and not the work of the Spirit in an institution or in particular rites. Secular world happens because God no longer has a place in human life. A religious becomes a secular person if he or she is "not afraid of God", "does not appreciate God", and "does not recognize God’s role in life". God is probably recognised, but God is far from the real life. To counter secularism in the rites and bridging the sacred and the profane worlds, rites should never be separated from life, the concept of life needs to be developed from the concept of the self as God's image, and the self-concept needs to be renewed constantly towards the direction of the integral self.